HUMAN RESOURCES MANAGER DECISION MAKING TOWARDS EMPLOYEES USING DATA MINING METHOD - Kusuma Wardhani, Nia; Windu Gata (Dinasti Publisher, 2022)
Important decisions in decision making in organizations are often initiated by Human Resources Managers, where data objects in the form of personal or employee must be complete and processed not by using feelings in decision making. If the forecast results in making decisions that are not right, it can result in the company not being ready to meet the future so that it has the potential to harm the company itself. Based on previous studies on Human Resource Management, this research was conducted by testing the Kaggle repository dataset using the Datamining methodology, where the results obtained can be used as an initial reference for a manager who makes decisions based on datasets from the company. Usually for data processing using qualitative and quantitative methods, but in this study using the Data Mining method using algorithms from machine learning, namely: Estimation, Prediction, Cluster, and Classification. It is hoped that the results of this research will enable Human Resource Managers as a basis for analysis to make decisions using Data Mining or Machine Learning as needed.